Report of the Working Group on Decentralised Planning and Panchayati Raj Institutions for the Tenth Five Year Plan (2002-2007) November 2001 - Planning Commission (Planning Commission, 2001)
Democratic decentralisation and involvement of people in decision-making process was recognized by the Constituent Assembly, which enshrined it in the Constitution as one of the Directive Principles of the State Policy. Several initiatives were taken in the 1950s and 1960s to promote democratic decentralisation. However, the 73rd and 74th Constitutional Amendment Acts mark a watershed in the history of governance in the country. Panchayati Raj Institutions (PRIs) were introduced as a distinct third tier of government. At the time of the formulation of the Ninth Five Year Plan, the 73rd & 74lh Amendment Acts were in the process of being operationalised. It was expected that PRIs that come up under the new Acts would be devolved functions, finances and the functionaries to enable them to emerge as institutions of self-government
Government of India Planning Commission New Delhi
Government of India Planning Commission
Keywords: Elections to Panchayats; Devolution of Powers; Authority and Responsibilities on Panchayats; Financial Devolution to Panchayats; District Planning Committees; Gram Sabha; Panchayats in Scheduled Areas; Role of Panchayati Raj Institutions in Centrally Sponsored Schemes; People’s Participation; Transparency; Accountability and Social Audit; Interface between Panchayati Raj Institutions and Voluntary Agencies; Women; Marginalised Groups and Panchayats